Sports science research and technology support : International Congress, icSPORTS 2013, Vilamoura, Algarve, Portugal, September 20-22, 2013. Revised selected papers /: International Congress, icSPORTS 2013, Vilamoura, Algarve, Portugal, September 20-22, 2013. Revised selected papers. (2015) - Unknown
No abstract available